(untitled) (Journal of Hama University, 2020)
In this study, a controlled release oral delivery system for ketoprofen was developed using the ionic gel method. Sodium alginate was used as a polymeric carrier and calcium chloride as a cross-linking agent. the aim of this study was to obtain delayed release spherical beads with better bioavailability and fewer side effects than conventional dosage forms. Ketoprofen was used as a model drug because of its common usage, side effects (irritant to gastric mucosa) and low solubility. The aim of this study was to suggest the best formula for preparing ketoprofen-loaded alginate beads, different concentrations of alginate (3%, 4%, 5%), and different ratios of alginate: drug (1: 1, 1: 3, 3: 1) were evaluated. The effect of adding of MC and HPMC were analyzed for their influence on delay of the rate of release of ketoprofen. The quality of prepared beads have been evaluated through some tests (weight, dimensions, shape, encapsulation efficiencies and drug release). it was concluded that raising the concentrations of alginate to 5% led to improving the encapsulation efficiencies and beads content of drug, but it led to delaying drug release too, using the ratio of alginate: drug (1: 3), both the beads content of drug and the encapsulation efficiencies improved, and no delay was observed in drug release when adding MC and HPMC, so the proposed formula is: sodium alginate at a concentration of 5% and ratio of alginate: drug (1: 3) and Calcium chloride (0.1 M).